The Portrayal of Beauty Privilege and Beauty Ideals in Snow White And The Seven Dwarfs - Nurul Istiqamah Kadekoh (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
This study explores the portrayal of beauty standards and beauty privilege in the classic fairy tale Snow White and the Seven Dwarfs, using a feminist literary approach and intersectionality theory. The tale, widely known through the Brothers Grimm version and its popular adaptations, continues to influence societal perceptions of beauty, particularly concerning women. The research is motivated by the need to critically examine how such narratives contribute to the normalization of idealized beauty and its impact on gender roles. In this tale, beauty is not only central to the protagonist’s identity but also determines how others treat her, reflecting how physical appearance can translate into unearned social advantages—a concept known as beauty privilege. The study employs a qualitative content analysis method, focusing on selected narrative elements and character interactions that emphasize Snow White's appearance. Using feminist literary criticism, the analysis investigates how Snow White's beauty becomes the primary source of her value, overshadowing traits such as intellect or agency. Meanwhile, intersectionality theory is used to examine how beauty interacts with other social factors, such as gender and age, to shape power dynamics and privileges in the story. The findings reveal that Snow White’s beauty repeatedly spares her life, earns her protection and admiration from strangers, and culminates in a marriage proposal. These privileges underline the societal inclination to reward those who conform to dominant beauty ideals. This study contributes to broader discussions on how literature perpetuates gendered beauty norms and their real-life implications on women’s roles and worth.